Āndhramahābhāratamu, upadēśamu - Gōpālakrṣṇamūrti, Nandula (Pratulaku, Nandula Rāmalakṣmi, 1982)
Study on moral and religious teachings in the Āndhramahābhāratamu, Telugu rendering of the Mahābhārata.